Determination of Optimum Conditions for Synthesis of Methyl Ester from Bleached Crude Palm Oil Using Sn-Zeolite and Red Mud Catalysts - Esi Amelyanti; Thamrin Usman; Winda Rahmalia (Universitas Diponegoro, 2023)
Methyl esters synthesis from bleached crude palm oil (BCPO) containing 0.36 and 20.86% of free fatty acids using Sn-zeolite and red mud has been done. This study aims to determine the esterification, transesterification, and transesterification-esterification simultaneous reactions optimum conditions when using Sn-zeolite, red mud, and Sn-zeolite-red mud mixture catalysts. The X-ray diffraction and Fourier transform infrared analysis results show that Sn has been impregnated on zeolite, indicated by cassiterite and Sn-O-Sn vibrational peaks in Sn-zeolite. The main component of red mud is NaCO3, indicated by analcite and carbonate peaks. Thin-layer chromatography results in the transesterification showed that red mud catalyst could totally convert triglycerides from BCPO to methyl ester when 5% catalyst, 3 hours, and CPO:methanol mole ratio 1:20 were used. In esterification, Sn-zeolite can synthesize methyl ester from low-quality CPO when using CPO:methanol mole ratio 1:20 for 3 hours, however, the conversion was not total. In the transesterification-esterification simultaneous, the conversion was also not total which the best reaction conditions at mixing Sn-zeolite:red mud 1.5:1 (w/w), 7% catalyst, and CPO:methanol mole ratio 1:20 for 3 hours. This study shows that esterification and transesterification processes can be carried out simultaneously at a particular mass ratio of Sn-zeolite and red mud.